2013
DOI: 10.1182/blood.v122.21.5336.5336
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Neutrophil: Lymphocyte Ratio Does Not Predict Survival In Multiple Myeloma Patients

Abstract: Background Cancer associated inflammation is one of the key determinants of outcome in patients with cancer. An elevated neutrophil: lymphocyte ratio (NLR) has been identified as a predictor of worse survival in patients with various solid tumors compared to hematologic malignancies but no reports yet examined its impact on multiple myeloma. The aim of this study was to examine the prognostic value of an elevated NLR in multiple myeloma. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
3
1
2
Order By: Relevance
“…In our study, no significant correlation was found between PLT level and both mortality and OS in patients with MM. However, similar to our study, some studies reported no significant relationship between the PLT level and OS (5,15).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, no significant correlation was found between PLT level and both mortality and OS in patients with MM. However, similar to our study, some studies reported no significant relationship between the PLT level and OS (5,15).…”
Section: Discussionsupporting
confidence: 86%
“…In our study, there was no relationship between the NLR and both mortality and OS in patients with MM. However, similar to our study, no significant correlation between NLR and mortality and OS was demonstrated in other studies (9,15).…”
Section: Discussionsupporting
confidence: 86%
“…They defended their result on the basis of small sample size (96 patients). [ 21 ] We also did not find any statistical significant relationship between OS and NLR groups, although the survival seems to be better in low NLR group but not statistically significant (5-year OS: 66% in low NLR, 54% in high NLR, P = 0.80). Due to these discrepancies, we think that prospective studies are needed, to clarify the effect of NLR on OS.…”
Section: Discussioncontrasting
confidence: 54%
“…In the literature, there are some discrepancies about the effect of NLR on OS in patients with hematologic malignancies. [ 10 11 20 21 ] Wongrakpanich et al . found a significant relationship between high NLR and OS in the patients with MM (NLR cutoff point 2.59).…”
Section: Discussionmentioning
confidence: 99%
“…The increased NLR levels of autologous‐transplanted patients with myeloma at day 100 (after reinfusion) also predicted reduced survival 12 . However, there are studies in the literature suggesting that the increased NLR may not be able to predict survival in patients with multiple myeloma 32,33 . In our study, increased NLR group presented significantly longer OS and PFS.…”
Section: Discussioncontrasting
confidence: 66%